SISTEM INFORMASI LAUNDRY BERBASIS WEB MENGGUNAKAN UML DAN MYSQL PADA LAUNDRY ASRAMA TGCU - Merdi Chrisdan Ndukonak; Listiarini Edy Sudiati; Moh Rofi (LPPM Politeknik Saint Paul Sorong, 2023)
The goal offthis research issto createeaalaundry informationnsystem capable of generating service needssfaster and easier. This laundry information system supports computerized transactionss.Theepurposeeoffthissstudyyisstooanalyzee theecurrentdsystem and create a web-based laundry information system in the TGCU Laundry Dormitory, to carry out transactions efficiently, so that it truly supports consumer orientation towards commercial services. To achieve this goal, the author discusses research methods, specifically: direct observations, interviews, documents and methods of system analysis and design. This system is designed using the UML model, while the programming languages ​​used are PHP and MySQL databases. The result of this information system design is to create a laundry information system that includes input, output and transaction data management for consumers tooachieveetheegoalloff thissresearchh, innorderrto be ableeto overcomeethe problemssthat exist in the TGCU Dormitory. Laundry. So, theeresult offthis searchhis “Web-based laundry information system using UML and MySQL in TGCU dormitory laundry”.